Method of path coefficients and OLS regression - Geary, R.C. (Economic & Social Studies, 1976)
Some time ago Sir Maurice Kendall suggested to the writer that a study of the theory and practice of path coefficients might be rewarding as shedding light on the still dark patches in the theory of relationship between random variables.
Keywords: Economics; Randomisation